Assessment of Sperm Function and Embryo Morphology Following Exposure to Peganum Harmala Seeds Decoction in Mice - Alghoul, Nagia; Sasi, Samira; Nuri Awayn; Ragil Prastiya; Khalid Salem (AlQalam Journal of Medical and Applied Sciences, 2025)
Harmala (Peganum harmala L.) is one medicinal plant used in traditional medicine for the treatment of a lot of diseases in many countries, including Libya. This study aimed to determine the effect of harmala plant seeds decoction on testosterone levels, sperm quality, and the embryos’ morphology. In this study, fifteen male mice were used at the age of 6 -10 weeks and divided into three groups (each group contained five mice). Group I (control) was given distilled water orally, while groups II and III received harmala plant seeds decoction at doses of 300 and 400 mg/kg, respectively, for three weeks. The results showed a significant decline in the mean body weight in the treated groups compared with the control, and also a significant increase in the percentage of abnormal sperm was observed in the group treated with a dose of 400 mg/kg. There was no effect of harmala seeds decoction on embryo morphology, the mean weight of testes, testosterone hormone, sperm counts, and its motility.